Batu Kapur sebagai Prekursor Hidroksiapatit: Tinjauan Metode Sintesis, Tantangan, dan Prospeknya - Nisa’atin Barkah; Romy Dwipa Yamesa Away (Lembaga Yasin AlSys, 2025)
Hydroxyapatite (HAp) is a calcium phosphate biomaterial with high biocompatibility, widely utilized in biomedical, cosmetic, and photocatalytic applications. The high production cost of synthetic HAp has driven the search for abundant and environmentally friendly natural alternatives, such as limestone (CaCO₃), as a potential precursor. This article aims to review various limestone-based HAp synthesis methods, including wet precipitation, sol-gel, hydrothermal, and sintering techniques, and to evaluate the influence of process parameters on the Ca/P ratio, phase purity, and crystal morphology. The review is conducted through an analysis of recent literature comparing the performance of each method. Findings indicate that limestone with CaCO₃ content exceeding 95% can produce HAp with a Ca/P ratio approaching the stoichiometric value of 1.67; however, the presence of natural impurities such as Si, Al, Mg, and Fe may lead to the formation of secondary phases, such as β-tricalcium phosphate (β-TCP). Optimization of process parameters, including calcination temperature, pH, and reaction time, is shown to be crucial for enhancing crystallinity and approximating the structure of natural bone. Furthermore, green synthesis approaches employing bio-extracts such as gelatin or leaf extracts contribute to improved homogeneity and particle size control. This review concludes that limestone is an economical and sustainable local source for HAp production, with significant potential for the development of biomimetic materials based on Indonesian natural minerals that are efficient and globally competitive.